Risk factors for work-related asthma in health workers with exposure to diverse cleaning agents in two African health care settings - Mwanga, Hussein Hassan (Department of Public Health and Family Medicine, 2020)
Background: Health workers (HWs) are exposed to a wide range of chemicals used for cleaning and disinfection. This has been largely attributed to the ever-increasing demand for effective cleaning and disinfection in hospital settings in an effort to prevent healthcare associated infections. Over the last two decades, there has been increasing evidence linking cleaning agents to adverse work-related health effects such as rhinitis, asthma and contact dermatitis. There is however little information on the specific cleaning agents and tasks associated with various asthma-related outcomes. Furthermore, limited information exists regarding exposure-response relationships between the frequency of exposure to specific cleaning agents and asthma-related outcomes. This study investigated the prevalence and risk factors for work-related asthma (WRA) among HWs exposed to diverse cleaning agents in two academic tertiary public hospitals in southern Africa - South Africa and Tanzania. Methods: A cross-sectional study of 699 HWs was conducted. Exposure assessment included systematic workplace observations, environmental sampling for aldehydes (orthophthalaldehyde-OPA, glutaraldehyde and formaldehyde) and urine biomonitoring for chlorhexidine. Environmental sampling for aldehydes was conducted more extensively in the South African hospital (SAH). A pilot sampling in the Tanzanian hospital (TAH) revealed very low detectable levels of OPA and glutaraldehyde and as a result extensive measurements were not done. In the SAH, a total of 269 full-shift passive personal samples were collected from 164 HWs randomly selected from 17 different clinical departments. Passive sampling used TraceAir® AT580 monitors (Assay Technology, Livermore, CA). Biomonitoring for chlorhexidine was only conducted in the SAH since none of the HWs in the TAH used chlorhexidine. For the health outcome assessment, a total of 697 HWs completed interviews using the ECRHS questionnaire adapted for occupational contexts, which contained in-depth information on asthma, as well as detailed information on tasks and chemicals used during the course of their work. Sera was successfully collected from 682 HWs and analysed for specific immunoglobulin E (sIgE) antibody reactivity to common aero-allergens (Phadiatop) and specific occupational allergens (NRL - Hevea brasiliensis (Hev b5, Hev b6.02), chlorhexidine and OPA). Methacholine challenge tests (MCT) were performed on all South African HWs (n=318), based on standard inclusion criteria. Spirometry, accompanied by a post-bronchodilator (post-BD) test was conducted on all Tanzanian HWs (n=329) and a small proportion (n=25) of South African HWs where MCT was contraindicated. All HWs from both hospitals (n=654) underwent fractional exhaled nitric oxide (FeNO) testing during the working day prior to spirometry. Results: The prevalence of current asthma was 10% (atopic asthma 6%, non-atopic asthma 4%), while 2% had WRA. The prevalence of atopy was 43%, with 4% of workers being sensitised to OPA, 2% to NRL and only 1% to chlorhexidine. Environmental sampling demonstrated that OPA was detectable in 6 (2%) samples, all samples (Geometric mean (GM) = 0.010 ppm) being higher than the ACGIH exposure limit (0.0001 ppm). Workers with detectable OPA were found to have a longer duration of OPA use (OR = 1.28; 95% CI: 1.10 – 1.50). Formaldehyde was detectable in 103 (38%) samples (GM = 0.005 ppm), with 1% of samples having levels higher than the NIOSH TWA exposure limit (0.016 ppm). Asthmarelated outcomes (increasing asthma symptom score and FeNO) demonstrated consistent positive associations with certain medical instrument cleaning agents (OPA, QACs and enzymatic cleaners) and tasks (pre-cleaning of medical instruments, changing sterilisation solutions and manual disinfection of medical instruments) as well as certain patient care activities (disinfection prior to procedures, cleaning/disinfecting wounds, application of wound dressing, usage of adhesives and adhesive removing solvents). A particularly pronounced dose-response relationship was observed between work-related ocular-nasal symptoms and medical instrument cleaning agents (OPA, glutaraldehdye, QACs, enzymatic cleaners, alcohols and bleach; OR range: 2.50 – 12.08) and tasks (OR range: 2.58 – 3.97). Furthermore, a strong association was observed between higher asthma symptom scores and use of more sprays than wipes for fixed surface cleaning activities (mean ratio = 3.00; 95% CI: 1.50 – 5.98). Conclusion: This study has demonstrated that detectable exposures to OPA are higher and more isolated to certain departments than the more widespread low-level formaldehyde exposures present throughout the hospitals. Furthermore, cleaning agents have replaced NRL as important causes for WRA in health settings. Finally, specific cleaning agents such as OPA, quaternary ammonium compounds and enzymatic cleaners associated with medical instrument cleaning/disinfection as well as patient care activities and the use of sprays for fixed surface cleaning, are important environmental risk factors for various asthma-related outcomes among HWs in health care settings.